Adiponectin predicts MMP‐2 activity independently of obesity. (October 2014) - Miksztowicz, Verónica; Fernandez Machulsky, Nahuel; Lucero, Diego; Fassio, Eduardo; Schreier, Laura; Berg, Gabriela
Abstract Background Matrix metalloproteinases (MMPs), especially MMP‐2 and MMP‐9, have been identified in atherosclerotic plaques and have been directly associated with plaque remodelling and vulnerability. Cardiovascular disease (CVD) is related to insulin resistance (IR) and obesity, characterized by changes in plasma levels of inflammatory markers, such as adiponectin and C‐reactive protein (CRP). Our aim was to evaluate the impact of both proteins on MMP‐2 and MMP‐9 behaviour in individuals with IR. Materials and methods Plasma MMP‐2 and MMP‐9 activity, adiponectin and hs‐CRP concentration and lipoprotein profile were determined in 52 patients with metabolic syndrome (MS) and 27 controls. Results Patients with MS presented significantly higher MMP‐2 activity than controls: 0·95 ± 0·12 vs. 0·77 ± 0·15 relative units (RU) (P < 0·001), while MMP‐9 activity was not detectable. MMP‐2 activity decreased across quartiles of adiponectin, being significantly reduced in individuals with the highest levels of adiponectin in compared with the lowest levels (0·75 ± 0·17 vs. 0·93 ± 0·09 RU, P < 0·005). This difference persisted significant after adjusting by obesity markers. MMP‐2 activity was significantly increased in individuals with the highest levels (G3) compared with those with the lowest levels (G1) of hs‐CRP (0·94 ± 0·12 vs. 0·86 ± 0·12, P = 0·041) Conclusion In this study, we observed that adiponectin levels predicted MMP‐2 plasma activity independently of obesity. This finding suggests that the inflammatory process, associated with the highest CVD risk, would be involved in MMPs vascular production.